Psychological changes following weight loss in overweight and obese adults: a prospective cohort study. - Sarah E Jackson; Andrew Steptoe; Rebecca J Beeken; Mika Kivimaki; Jane Wardle (PLoS ONE)
Background Participation in weight loss programs is often associated with improved wellbeing alongside reduced cardio-metabolic risk. In contrast, population-based analyses have found no evidence of psychological benefits of weight loss, but this may be due to inclusion of healthy-weight individuals. We therefore examined cardio-metabolic and psychological changes following weight loss in a cohort of overweight/obese adults. Methods Data were from 1,979 overweight and obese adults (BMI ≥ 25 kg/m(2); age ≥ 50 y), free of long-standing illness or clinical depression at baseline, from the English Longitudinal Study of Ageing. Participants were grouped according to four-year weight change into those losing ≥ 5% weight, those gaining ≥ 5%, and those whose weight was stable within 5%. Logistic regression examined changes in depressed mood (eight-item Center for Epidemiologic Studies Depression score ≥ 4), low wellbeing (Satisfaction With Life Scale score <20), hypertension (systolic blood pressure ≥ 140 mmHg or anti-hypertensives), and high triglycerides (≥ 1.7 mmol/l), controlling for demographic variables, weight loss intention, and baseline characteristics. Results The proportion of participants with depressed mood increased more in the weight loss than weight stable or weight gain groups (+289%, +86%, +62% respectively; odds ratio [OR] for weight loss vs. weight stable = 1.78 [95% CI 1.29-2.47]). The proportion with low wellbeing also increased more in the weight loss group (+31%, +22%, -4%), but the difference was not statistically significant (OR = 1.16 [0.81-1.66]). Hypertension and high triglyceride prevalence decreased in weight losers and increased in weight gainers (-28%, 4%, +18%; OR = 0.61 [0.45-0.83]; -47%, -13%, +5%; OR = 0.41 [0.28-0.60]). All effects persisted in analyses adjusting for illness and life stress during the weight loss period. Conclusions Weight loss over four years in initially healthy overweight/obese older adults was associated with reduction in cardio-metabolic risk but no psychological benefit, even when changes in health and life stresses were accounted for. These results highlight the need to investigate the emotional consequences of weight loss.